Genetic Mapping of a Defective Bacteriophage on the Chromosome of Bacillus subtilis 168 - Garro, Anthony J. (1970)
A genetic marker responsible for the killing activity of PBSX, a defective phage carried by Bacillus subtilis 168, has been located on the bacterial chromosome. Two mutant strains of B. subtilis 168, which produced tailless phage particles upon mitomycin C induction, were shown to carry lesions, designated xtl-1 and xtl-2, which were linked by transformation and PBS1-mediated transduction to metC. The link-age relationship between xtl and adjacent auxotrophic markers was determined by three-factor PBS1 transduction, the suggested order of markers being argO 1 metA metC xtl.